Filosofía de la historia, utopías y proyecto de los Pasajes en Walter Benjamin: algunas claves teórico metodológicas - Alejandro Casas (Eleuthera)
Some significant elements of Walter Benjamin’s philosophy of history are presented, based on his conceptualization of historical time and a particular configuration between past, present and future, from his messianic perspective and with a focus on utopias. To do this, we will present some of Benjamin’s dialectical categories and images, based fundamentally on some more mature and political works such as the Arcades Project, in addition to the theses of On the Concept of History.The proposal is located from a first advance –in this case individual– of the Collective Project of Uruguay within the framework of the Social Service in History program, on “Social issue, social struggles and Social Work in Uruguay from the origins of the dictatorship to the neoliberalism”. It will seek to contribute with some reflections and theoretical-methodological categories for the subsequent study of socio-historical processes, social struggles and social work.